Correlation between Microalbuminuria and Coronary Angiographic Severity in Non-diabetic Myocardial Infarction patients - Islam, Mohammad Mamoon; Akanda, Abdul Kader; Ullah, Mohammad; Alam, Md Shariful; Mostofa, Md Gulam; Rahman, Md Zillur; Ali, Md Bonday; Basak, Suchitra (Cardiovascular Journal, 2022)
Background: Microalbuminuria may have an association with myocardial infarction in absence of traditional risk factors like diabetes. The present study was intended to find the association between microalbuminuria and angiographic severity of coronary artery disease in non-diabetic myocardial infarction patients. Methods: This cross sectional analytical study included 105 non-diabetic patients with myocardial infarction who underwent coronary angiography (CAG). The microalbuminuria was defined as urine albumin to creatinine ratio (ACR) of 30 -300 mg/g, while angiographic severity was measured by Gensini score with score e” 36 was taken as moderate to severe coronary artery disease (Group I) and score below 36 was termed as absent or mild coronary artery disease (Group II). Association of microalbuminuria with severity of coronary artery disease was determined. Results: Presence of microalbuminuria was found significantly higher (45%) in patients with moderate to severe coronary artery disease than that in patients with absent or mild CAD (4.6%). The Odds of having moderate to severe coronary artery disease in patients with microalbuminuria was observed to be 17 times (95% CI = 4.5 - 63) higher than that in patients without having this condition. Correlation between ACR and Gensini score was also found a significant positive relationship (r=0.702, p<0.001) with 70% of variation in Gensini score being explained by ACR. Conclusion: Microalbuminuria can be considered as a predictor of the severity of coronary artery disease in non-diabetic myocardial infarction patients. Cardiovasc j 2022; 15(1): 56-62